8a-6+2a=-2+6a

Simple and best practice solution for 8a-6+2a=-2+6a equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8a-6+2a=-2+6a equation:


Simplifying
8a + -6 + 2a = -2 + 6a

Reorder the terms:
-6 + 8a + 2a = -2 + 6a

Combine like terms: 8a + 2a = 10a
-6 + 10a = -2 + 6a

Solving
-6 + 10a = -2 + 6a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6a' to each side of the equation.
-6 + 10a + -6a = -2 + 6a + -6a

Combine like terms: 10a + -6a = 4a
-6 + 4a = -2 + 6a + -6a

Combine like terms: 6a + -6a = 0
-6 + 4a = -2 + 0
-6 + 4a = -2

Add '6' to each side of the equation.
-6 + 6 + 4a = -2 + 6

Combine like terms: -6 + 6 = 0
0 + 4a = -2 + 6
4a = -2 + 6

Combine like terms: -2 + 6 = 4
4a = 4

Divide each side by '4'.
a = 1

Simplifying
a = 1

See similar equations:

| 4x=256 | | 5(a+2)+3(2a-1)= | | 6z=24 | | 10x=100000 | | 3y-2*11=(5)6y+5 | | 3-t=1 | | 9x=729 | | 11=2x+17 | | 3y-2*11=6y+5*5 | | 3.7(-87x-3)=3.7(7x-30) | | 8a^2+8+16a= | | 0.16(36-24x)=0.66(9-6x) | | 7b-2+3b=30+6b | | 4x=4096 | | -13-3z=12-4y | | y+14=3y+2 | | x-7*x*450=0 | | 0.16(36-24x)=0.66 | | 2x=1024 | | 2.5+8= | | z*3=2*(z+1) | | 7(9n+9)=315 | | 2x+4.5=21 | | 18x^2+216=0 | | ax+bk=t | | z*3=2*z+1 | | 7x^2-12x^2+5=0 | | 20-5m=45 | | -6a-(4b-12a+7c)= | | 2(2+3x)+2(2x-1)=3(x+6) | | 729=0 | | 7x+37=149 |

Equations solver categories